Continuous positive airway pressure: Physiology and comparison of devices. Issue 3 (June 2016) - Gupta, Samir; Donn, Steven M.
Summary: Nasal continuous positive airway pressure (CPAP) is increasingly used for respiratory support in preterm babies at birth and after extubation from mechanical ventilation. Various CPAP devices are available for use that can be broadly grouped into continuous flow and variable flow. There are potential physiologic differences between these CPAP systems and the choice of a CPAP device is too often guided by individual expertise and experience rather than by evidence. When interpreting the evidence clinicians should take into account the pressure generation sources, nasal interface, and the factors affecting the delivery of pressure, such as mouth position and respiratory drive. With increasing use of these devices, better monitoring techniques are required to assess the efficacy and early recognition of babies who are failing and in need of escalated support.